Global environmental change : research pathways for the next decade (National Academy Press, 1999)
"This volume encourages a renewed commitment to understanding global change and sets a direction for research in the decade ahead. Through case studies the book explores what can be learned from the lessons of the past 20 years and what are the outstanding scientific questions."--Catalog description